A Novel Double Side Branch Protection Technique for a Left Main Trifurcation Lesion: Simultaneous Jailed Balloon and Jailed Corsair Technique. (13th September 2018) - Munakata, Masahito; Numasawa, Yohei; Ishikawa, Shiro; Koyama, Takashi
Abstract : Percutaneous coronary intervention for left main trifurcation disease is challenging. Although side branch protection techniques such as the jailed balloon technique and jailed Corsair technique are the established methods for treatment of coronary bifurcation lesions, little is known regarding the application and feasibility of these techniques for left main trifurcation disease. We herein describe a 72-year-old man with angina pectoris who was successfully treated with percutaneous coronary stent implantation for a left main trifurcation lesion. In this case, we performed a novel double side branch protection technique, the simultaneous jailed balloon and jailed Corsair technique, with a single 8 Fr guiding catheter. This is the first case report to highlight the feasibility and efficacy of combined use of the jailed balloon and jailed Corsair techniques during percutaneous coronary intervention for left main trifurcation disease.